2014
DOI: 10.1039/c4nr00693c
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur doping: a facile approach to tune the electronic structure and optical properties of graphene quantum dots

Abstract: Sulphur-doped carbon-based materials have attracted a great deal of interest because of their important applications in the fields of oxygen reduction reactions, hydrogen storage, supercapacitors, photocatalysts and lithium ion batteries. Here, we report a new member of sulphur-doped carbon-based materials, i.e. sulphur doped graphene quantum dots (S-GQDs). The S-GQDs were prepared by a hydrothermal method using fructose and sulphuric acid as source materials. Absorption and photoluminescence investigations sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
174
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(189 citation statements)
references
References 23 publications
14
174
0
1
Order By: Relevance
“…These two FLE peaks correspond well to that of UV-vis absorption peaks at 211 and 268 nm. The red shift of peaks from absorption spectra to FLE spectra can be observed in previous reports of GQDs [34], S-GQDs [35], and Cl-GQDs [36], suggesting that the FLE peak corresponds to the ground vibrational state (GVS) and the peak of UV-vis absorption corresponds to the highest vibrational state (HVS) in the same excited state: GVS of C π* is 5.25 eV, GVS of N π* 4.38 eV, HVS of C π* 5.88 eV, and HVS of N π* 4.63 eV. When NGQDs absorb high-energy photons, electron transition from C π to C π* may be caused, and then the internal conversion (C π*→N π*→O π*) results in FL emission (O π*→C π).…”
Section: Resultsmentioning
confidence: 70%
“…These two FLE peaks correspond well to that of UV-vis absorption peaks at 211 and 268 nm. The red shift of peaks from absorption spectra to FLE spectra can be observed in previous reports of GQDs [34], S-GQDs [35], and Cl-GQDs [36], suggesting that the FLE peak corresponds to the ground vibrational state (GVS) and the peak of UV-vis absorption corresponds to the highest vibrational state (HVS) in the same excited state: GVS of C π* is 5.25 eV, GVS of N π* 4.38 eV, HVS of C π* 5.88 eV, and HVS of N π* 4.63 eV. When NGQDs absorb high-energy photons, electron transition from C π to C π* may be caused, and then the internal conversion (C π*→N π*→O π*) results in FL emission (O π*→C π).…”
Section: Resultsmentioning
confidence: 70%
“…Based on the PL and PLE experimental results, an energy band diagram for K-GQDs is proposed ( Figure 5) to illustrate the electron transitions in the process of excitation and emission. Electron transitions may take place when high energy photons is absorbed, followed by emitting a number of low energy photons after undergoing interband crossing 7 and vibration relaxation. The introduction of new energy levels is the key for the fine-tuning of the optoelectronic properties of GQDs, which is important to make GQDs suitable for different applications.…”
Section: Resultsmentioning
confidence: 99%
“…6 Previous studies have shown that doping of hetero-atoms into the GQDs is an effective way to alter the band gap or introduce new energy levels into the GQDs which can be used to tune the PL properties in order to make GQDs suitable for various applications. 7 Up to date, research efforts have been mainly focused on doping non-metallic atoms like nitrogen, 8 sulphur, 7,9 chlorine, 10 fluorine 11 and selenium 12 into GQDs. Some works have also been reported for co-doped GQDs like B, N-doped GQDs, 13 N, S-doped GQDs, 14 and N, P-doped GQDs.…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to previous reports where multiple PLE bands contribute to one emission, which means cross-band interactions exist in the S-doped GQDs. [ 30 ] Figure S5 in the Supporting Information shows the PL spectra of two kinds of N-doped GQDs emitting blue and green light under UV and visible light excitation, respectively. Only green light is emitted under UV and visible light excitation when these two N-GQDs are physically mixed together.…”
Section: Optical Properties Of Sn-gqdsmentioning
confidence: 99%